Elucidating endothelial pathology in polypoidal choroidal vasculopathy : a patient-derived cellular model approach - Yeo, Natalie Jia Ying (Nanyang Technological University, 2022)
Polypoidal choroidal vasculopathy (PCV), an Asian-predisposed ocular disease subtype, is characterized by haemorrhagic and polyp-like dilatations of blood vessels in the choroid. Using human blood outgrowth endothelial cells (BOECs) for disease modelling, we performed RNA-sequencing on PCV and normal BOECs in response to heterogeneous flow as a disease-relevant stressor. Functionally, PCV BOECs displayed repressed mitochondrial function and abnormal superoxide increases under heterogeneous flow stress. Notably, transcriptomic analyses revealed intrinsic endothelial perturbations of cell adhesion and extracellular matrix (ECM) organization in PCV, as well as downregulated CLDN5 that is a tight junction component. Functionally, baseline PCV BOECs exhibited lower transendothelial electrical resistance, suggesting decreased barrier integrity. In conclusion, ECM regulation and barrier dysfunction may underlie PCV polyp formation with altered mitochondrial flow responses exacerbating endothelial dysfunction upon turbulent flow. This thesis describes a novel endothelial cellular model for PCV and highlights endothelial phenotypes amenable to therapeutic restoration.